Safety and efficacy of a feed additive consisting of Lactiplantibacillus plantarum NCIMB 30148 for all animal species (Genus Breeding Ltd.) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of Lactiplantibacillus plantarum NCIMB 30148 as a technological additive to improve ensiling of fresh plant material. The additive is intended for use in all fresh material for all animal species at a proposed minimum concentration of 1 × 109 colony forming units (CFU)/kg fresh plant material. The bacterial species L. plantarum is considered by EFSA to be suitable for the qualified presumption of safety approach to safety assessment. The identity of the strain was established, and no antimicrobial resistance genes of concern were detected. Therefore, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concluded that the use of the strain as a silage additive is considered safe for all the animal species, for consumers of products from animals fed with the treated silage and for the environment. Regarding user safety, the additive should be considered as a potential skin and respiratory sensitiser, and any exposure through skin and respiratory tract is considered a risk. The additive is not a skin irritant, but the Panel cannot conclude on the eye irritation potential of the additive. The FEEDAP Panel concluded that the addition of L. plantarum NCIMB 30148 at a minimum level of 1 × 109 CFU/kg fresh plant material has the potential to improve the production of silage from fresh material.